Analisis Pengetahuan dan Ketuntasan Siswa pada Materi Bioteknologi di SMA Negeri Se-Kota Binjai - Rangkuti, Sailana Mira; Harahap, Fauziyah; Edi, Syahmi (Jurnal Pendidikan Biologi, 2016)
This research aimed to determined; (1) the level of studentâ knowledgeÂ  on biotechnology subject matter; (2) the level studentâ completeness on biotechnology subject matter. This research was descriptive qualitative research. The population of this research were gradeÂ  XII student from 5 senior high school in Binjai including SMA Negeri 1, SMA Negeri 2, SMA Negeri 4, SMA Negeri 6, SMA Negeri 7. Samples were chosen by using random sampling technique. Data were collecting using instrument of diagnostic test mastery on matter biotechnology and interview. The data were analyzed using descriptive percentage. Result from this research showed: (1) the average level of studentâ knowledgeÂ  on biotechnology subject matter wasÂ  68,15 (SDÂ±15,24) and categorized as good. (2) the level of studentâ completeness on biotechnology subject matter was (36,32%). Based on the result of this research it can concluded the level of knowledge of students is actegorized as good but still important to improve the level of knowledge and attitude learning difficulties for more goodness result.